Kompatibilitas Spora Glomus Hasil Isolasi dari Rizosfer Macaranga triloba dengan Tiga Jenis Tanaman Inang - Gian Wulandari; - Suwirmen; Zozy Aneloi Noli (Universitas Andalas, 2014)
The study about compatibility of Glomus spores isolated from the rhizosphere Macaranga triloba with three types of host plants have been done from February to November 2013 in greenhouses and Plant Physiology Laboratory, Department of Biology, Andalas University, Padang. The aim of this study was to determine compatibility of corn (Zea mays), jatropha (Jatropha curcas) and scallion (Allium fistulosum) as host plants of Glomus spores isolated from the rhizosphere Macaranga triloba. This experiment used completely randomized design (CRD) with 3 treatments and 9 replications. The treatments were corn, jatropha and scallion. The results showed that spore density of the corn and scallion gave the same effect, whereas jatropha gave different effects on the two plants. The degree of infection of corn roots and scallion showed a high criteria, while the percentage degree of infection on jatropha roots showed a moderate criteria. The corn and scallion were compatible host plants of Glomus spores isolated from the rhizosphere of Macaranga triloba.Key words: compatibility, host plants, Glomus spores